2011
DOI: 10.1155/2011/745090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Do Bugs Need Drugs? Program in British Columbia: Can We Curb Antibiotic Prescribing?

Abstract: The Do Bugs Need Drugs? program significantly improves physician antibiotic prescription decisions and is ecologically associated with desirable change in population antibiotic consumption patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 23 publications
(14 reference statements)
0
53
0
1
Order By: Relevance
“…Madle et al have shown that web based teaching materials can change knowledge and attitudes regarding antibiotic use [48]. An educational program directed at both health professionals and the general public in Canada was associated with a decline in antibiotic prescribing rates, as reported by McKay [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Madle et al have shown that web based teaching materials can change knowledge and attitudes regarding antibiotic use [48]. An educational program directed at both health professionals and the general public in Canada was associated with a decline in antibiotic prescribing rates, as reported by McKay [49]. …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, HIV prevalence is 18% and 11% among MSM in Toronto and Ottawa, respectively [6,7] suggesting that HIV-positive men are over-represented in syphilis transmission networks. For men co-infected with HIV, the response to syphilis treatment can be suboptimal, [8] the development of neurosyphilis may be accelerated, [9] treatment decisions are more complex, and HIV infectiousness may be enhanced [10]. Prompt syphilis testing and treatment is important to prevent potential clinical sequelae and also to limit ongoing syphilis and HIV transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Il a été démontré que l'antibiothérapie inutile représente un lourd fardeau de l'utilisation inappropriée des antimicrobiens au Canada (1-4). En raison de préoccupations croissantes à propos du lien entre l'utilisation d'antimicrobiens et la résistance aux antimicrobiens, une réorientation vers une utilisation plus prudente des antimicrobiens a été l'un des domaines mis en évidence pour la lutte contre la propagation de la résistance aux antimicrobiens (5)(6)(7)(8).…”
Section: Discussionunclassified